Al-Mafhūm al-Asāsiyy li-Tatwīr al-Mawād al-Ta'līmīyah - Esti Indi Astuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Learning material is one of important things in a teaching and learning process. A good learning material is the one which is appropriate with the condition of the students. Therefore, it is necessary for all teachers to know how to develop a good learning material to make it suitable for the students in each level. This article conducts the basic concept of learning material development which consists of definition, characteristics, kinds and function of learning material, how to develop it and apply it well.